Effects of Three-Axial Material Inhomogeneity on Lengthwise Cracks in Non-Linear Elastic Beams - RIZOV, Victor Iliev (Engineering Transactions, 2019)
The present paper investigates lengthwise crack behaviour in three-axial inhomogeneous non-linear elastic cantilever beams, i.e., beams which exhibit inhomogeneous material properties along the width, height and length. The non-linear mechanical behaviour of the inhomogeneous material is described by the Ramberg-Osgood equation assuming that the modulus of elasticity varies linearly along the width, height and length of beams. A solution to the strain energy release rate is derived by considering the balance of the energy. The results obtained in the present paper indicate that the three-axial inhomogeneous material properties have a significant influence on the strain energy release rate in non-linear elastic beams.